2006
DOI: 10.1080/00927870600636936
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of a Noncommutative Ring

Abstract: R is any ring with identity. Let Spec r R resp. Spec R be the set of all prime right ideals resp. all prime ideals of R and let U r eR = P ∈ Spec r R e P . In this article, we study the relationships among various ring-theoretic properties and topological conditions on Spec r R with weak Zariski topology . A ring R is called Abelian if all idempotents in R are central see Goodearl, 1991 . A ring R is called 2-primal if every nilpotent element is in the prime radical of R see Lam, 2001 . It will be shown that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Let Spec r (R) be the set of all prime right ideals of R. It has been shown in Corollary 2.8 of [5], that if R is not a right quasi-duo ring, then Spec r (R) is a space with the weak Zariski topology but not with the Zariski topology. The weak Zariski topology on Spec r (R) has also been studied in [4,6]. Then τ contains the empty set and Spec r (R).…”
Section: Preliminariesmentioning
confidence: 98%
See 1 more Smart Citation
“…Let Spec r (R) be the set of all prime right ideals of R. It has been shown in Corollary 2.8 of [5], that if R is not a right quasi-duo ring, then Spec r (R) is a space with the weak Zariski topology but not with the Zariski topology. The weak Zariski topology on Spec r (R) has also been studied in [4,6]. Then τ contains the empty set and Spec r (R).…”
Section: Preliminariesmentioning
confidence: 98%
“…Remark. In Theorem 3.5 of [6], it has been shown that the set {U r (e)|e ∈ Id(R)} consists of all the clopen sets in Spec r (R).…”
Section: Preliminariesmentioning
confidence: 99%
“…In this article we introduce and study Zariski topology on the set Spec(M) of all prime submodule elements of an le-module R M. It is well established that the Zariski topology on prime spectrum is a very efficient tool to give geometric interpretation of the arithmetic in rings [2], [14], [25], [29], [36] and modules [1], [5], [6], [12], [13], [22], [23], [24], [26]. Here we have extended several results on Zariski topology in modules to le-modules.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the mathematical literature, knowing the prime and primitive spectra of rings (also of associative, Lie and Jordan algebras, etc) has been crucial in order to succeed to give structural theorems (or in order to simply gain a better understanding of the given algebraic system). Classically, one of the uses of the prime spectrum for commutative rings is to carry information over from Algebra to Topology and vice versa via the so-called Zariski topology (several generalizations of this construction for noncommutative rings have been achieved [17,24]). As for the primitive ideals of a ring, they naturally correspond to the irreducible representations of it, which in turn represent unquestionable tools in their analysis.…”
Section: Introductionmentioning
confidence: 99%